Observations of Budapest since 1992 - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 2012)
My wife, Susan, and I flew into Budapest from Moscow in the summer of 1992. It was our first visit to one of the former “satellites” of the USSR, although by 1992 we had spent a good deal of time in the Soviet Union – and then Russia. My work on a joint university project in Moscow had been difficult because of the dramatic changes taking place almost daily in the early 1990s, and we were looking forward to a few days of relaxed tourism in a country that was new to us. I also was intrigued by the plans for the new Central European University and was looking forward to meeting colleagues who would tell me more about the new university and their aspirations.